High Affinity Binding of Escherichia coli Cytotoxic Necrotizing Factor 1 (CNF1) to Lu/BCAM Adhesion Glycoprotein - Franziska Reppin; Sylvie Cochet; Wassim El Nemer; Günter Fritz; Gudula Schmidt (Toxins, 2017)
The protein toxin Cytotoxic Necrotizing Factor 1 (CNF1) is a major virulence factor of pathogenic Escherichia coli strains. It belongs to a family of single chain AB-toxins, which enter mammalian cells by receptor-mediated endocytosis. Recently, we identified the Lutheran (Lu) adhesion glycoprotein/basal cell adhesion molecule (BCAM) as a cellular receptor for CNF1. Here, we identified the Ig-like domain 2 of Lu/BCAM as main interaction site of the toxin by direct protein-protein interaction and competition studies. Using surface plasmon resonance, we showed a high affinity CNF-Lu/BCAM interaction with a KD of 2.8 nM. Furthermore, we performed small-angle X-ray scattering to define the molecular envelope of the Lu/BCAM-CNF1 complex, suggesting a 6:1 ratio of Lu/BCAM to CNF1 in the receptor-toxin complex. This study leads to a deeper understanding of the interaction between CNF1 and Lu/BCAM, and presents novel opportunities for the development of future anti-toxin strategies.